Working Long Hours and Having No Choice: Time Poverty in Guinea - Bardasi, Elena; Wodon, Quentin (2012)
This contribution provides a new definition of time poverty as working long hours without choice because an individual's household is poor or would be at risk of falling into poverty if the individual reduced her working hours below a certain time-poverty line. Time poverty is thus understood as the lack of enough time for rest and leisure after accounting for the time that has to be spent working, whether in the labor market, doing domestic work, or performing other activities such as fetching water and wood. The study applies the concepts used in the traditional poverty literature to measure time poverty defined in this new way to analyze its determinants in Guinea from 2002 to 2003. It finds that women are more likely to be time poor than men in Guinea, and even more so according to this new definition.